2012
DOI: 10.3342/ceo.2012.5.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Follow-up Results after Newborn Hearing Screening Program

Abstract: ObjectivesTo investigate the validity of newborn hearing screening protocol using automated auditory brainstem response (AABR) with a confirmation method using click auditory brainstem response (ABR) and to evaluate changes in hearing status of infants with confirmed congenital hearing loss.MethodsNeonates in the well-baby nursery were screened by staged AABR. Subjects whose final AABR result was "refer" were tested by diagnostic click ABR and 226 Hz tympanometry within 3 months of age. Changes in hearing stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
2
19
0
1
Order By: Relevance
“…This result is similar to that of a study carried out in a maternity ward in the city of Marília, State of São Paulo (22) . It is also similar to other studies carried out in other countries/cities, such as Napoles in Italy (23) , with reports of 75% coverage, in the State of New York, with 89% coverage (24) and in Soul, Korea, with 80% coverage (25) . In all the studies, indices are below the indicators cited in the Multi-Professional Committee for Hearing Health (COMUSA) (3) , which suggests: coverage of NHS in at least 95% of newborns, with the aim of achieving 100%, and of the Health Care Guidelines for Children of the Municipality, which determine universal attendance for all newborns with realization of NHS within the first month of life of neonates, or up to the third months for infants (corrected age), taking into account premature babies and those with long periods of hospitalization (14) .…”
Section: Discussionsupporting
confidence: 74%
“…This result is similar to that of a study carried out in a maternity ward in the city of Marília, State of São Paulo (22) . It is also similar to other studies carried out in other countries/cities, such as Napoles in Italy (23) , with reports of 75% coverage, in the State of New York, with 89% coverage (24) and in Soul, Korea, with 80% coverage (25) . In all the studies, indices are below the indicators cited in the Multi-Professional Committee for Hearing Health (COMUSA) (3) , which suggests: coverage of NHS in at least 95% of newborns, with the aim of achieving 100%, and of the Health Care Guidelines for Children of the Municipality, which determine universal attendance for all newborns with realization of NHS within the first month of life of neonates, or up to the third months for infants (corrected age), taking into account premature babies and those with long periods of hospitalization (14) .…”
Section: Discussionsupporting
confidence: 74%
“…32 Prior research has found abnormal audiological findings in 38% of patients who failed NHS in the well-baby nursery. 13 The positive predictive value depends on pretest probability, so newborns with MMC may be less likely to have false-positive NHS results. Automated ABR testing in NHS offers multiple logistic benefits over diagnostic ABR testing for predicting future brainstem dysfunction.…”
Section: Newborn Hearing Screening In Patients With MMCmentioning
confidence: 99%
“…The magnitude of this difference is underscored by the overall rarity of NHS failure, reported to be 3% and 1% for newborns in the NICU and well-baby nursery, respectively. 3,13 In comparison, patients with MMC who remained asymptomatic rarely failed NHS (4%, 1 of 27 patients). Given the high 0 20 20 5 pass 0 20 17 0 0 6 pass 1 0 0 7 pass 1 0 0 1 0 8 pass 0 0 9 pass 0 18 0 14 0 10 pass 2 0 0 11 pass 1 1 12 pass 0 1 1 13 pass 0 3 3 prevalence of ABR IPL abnormalities in patients with MMC but without brainstem symptoms, 6 NHS appears to be more specific than diagnostic ABR testing as a marker for brainstem dysfunction.…”
Section: Newborn Hearing Screening In Patients With MMCmentioning
confidence: 99%
“…In the last few years, an improvement over time with regards to initial hearing thresholds in infants who failed newborn hearing screening has been reported in several studies 1289 . Changes in hearing threshold in infants can depend on factors temporary affecting the auditory periphery as well the neural pathway and/or on a delay in “auditory maturation” 9-11 .…”
Section: Introductionmentioning
confidence: 96%